(untitled) (CIPEEX, 2022)
WITH THE INCREASING AGING OF THE POPULATION, A NEW PROFILE OF DISEASES IS GAINING PROMINENCE: NEURODEGENERATIVE AND CHRONIC DISEASES. IN THIS CONTEXT, ALZHEIMER’S DISEASE (AD) STANDS OUT, WHICH, ACCORDING TO THE WORLD HEALTH ORGANIZATION (WHO), IS THE MOST COMMON FORM OF DEMENTIA AMONG THE ELDERLY. AS THERE IS NO CURE, THE TREATMENT FOR THIS PATHOLOGY AIMS TO STABILIZE ITS SYMPTOMS AND PREVENT ITS PROGRESSION, THROUGH BOTH PHARMACOLOGICAL AND NON-PHARMACOLOGICAL MEASURES. THIS SYSTEMATIC LITERATURE REVIEW AIMS TO ANALYZE THE THERAPEUTIC OPTIONS AVAILABLE FOR THE TREATMENT OF AD. THE ARTICLES USED WERE SELECTED FROM SOURCES OF SCIENTIFIC EVIDENCE, THE SEARCH WAS SYSTEMATIZED, EVALUATING THE QUALITIES AND VALIDITY OF THE STUDIES. THE INCLUSION CRITERIA WERE RANDOMIZED CLINICAL TRIALS THAT FELL WITHIN THE YEARS 2015 TO 2021, AND COULD BE PUBLISHED OR UNPUBLISHED. EXCLUSION CRITERIA WERE DUPLICATE ARTICLES THAT DID NOT FIT INTO THE CLINICAL OUTCOME AIMED AT IN THE REVIEW, WHICH IS TO SHOW THE EFFECTIVENESS OF SPECIFIC DRUGS FOR AD. THE SEARCH STRATEGIES USED INCLUDED THE COCHRANE CONTROLLED TRIAL REGISTER (CCTR), NATIONAL LIBRARY OF MEDICINE (MEDLINE/PUBMED) AND LATIN AMERICAN AND CARIBBEAN HEALTH SCIENCES LITERATURE (LILACS). AMONG THE 96 ARTICLES FOUND IN THE LILACS, SCIELO AND PUBMED DATABASES, ONLY 38 ARTICLES WERE INCLUDED AFTER DISTINGUISHING AND ANALYZING THE ELIGIBILITY CRITERIA, WITH THE REST BEING WITHIN THE EXCLUSION CRITERIA. THESE 38 ARTICLES, AFTER AN APPROPRIATE SEARCH AND APPLICATION OF THE INCLUSION CRITERIA, WERE READ IN FULL FOR THE PREPARATION OF THE PRESENT STUDY. THIS STUDY ALLOWED A GLOBAL VIEW OF THE PHARMACOLOGICAL TREATMENTS INVOLVED IN AD THROUGH A SYSTEMATIC METHODOLOGY, HAVING ACHIEVED THE GENERAL AND SPECIFIC OBJECTIVES OF THIS REVIEW. IN VIEW OF THE FINDINGS OF THIS ANALYSIS, THE ANALYZED DRUGS MOSTLY PRESENTED POSITIVE OUTCOMES IN THE FACE OF THE MOST DIVERSE PARAMETERS USED, HOWEVER, CERTAIN RESULTS OF SOME STUDIES ARE STILL UNDER ANALYSIS FOR FURTHER RESEARCH, WHILE OTHERS PROVED TO BE NEGATIVE. FINALLY, THE NEED FOR MORE RESEARCH ON THE SUBJECT IS HIGHLIGHTED, CONSIDERING THE POSSIBILITY OF BASING AN EFFECTIVE TREATMENT FOR AD AND THUS IMPROVING THE QUALITY OF LIFE AND ASSISTANCE OF HEALTH PROFESSIONALS IN THIS DISEASE.